Old Raised Beaches and Dune Ridges Evidence from Kiriyankalli to Mundal in Northwest Sri Lanka - Katupotha, K.N.J. (My University, 2014)
Old raised beach and dune ridge formations in the Northwestern coastal zone from Kiryankalli to Mundal are the most distinctive members of the Quaternary System, not only in appearance but also in their topographic expression. It is essentially a clayey sand or loam with characteristic brick-red colour, and forms a number of low, narrow elongated ridges or domes. Due to their brick-red colour these formations are designated as Red Beds. Well developed deposits of Red Beds are noticed from the Baththulu Oya Bridge to Puttalam, and beyond that to Kudremalai. The origin of these Red Beds and dune ridges extends back to the Quaternary Period. Essentially an outcome of sea level and climatic changes of that time the Red Bed ridges show sequential changes. The overburden sandy layers in Red Bed dune ridges have been transported by wind action. The red colour of the sand is due to iron oxides mainly ferric and sand reddening due to the time factor. Likewise, it is possible to infer that the colloidal silicaceous material mixed with calcareous material of marine or lagoonal fauna, especially shells, demarcate the limit of paleo marine and terrestrial boundaries between the Quaternary and Neogene Periods.
Keywords: Raised beaches; Dune ridges; Kiriyankalli; Mundal; Northwest Sri Lanka